A Book Review on Reconstructing Celebrity Endorsement: Unveiling New Operations in Marketing and Consumer Behavior - Santhosh Kumar, K; Vinod, Divya (International Research Journal of Parroha, 2025)
This review seriously examines Mishra’s book, Reconstructing celebrity endorsement: Unveiling new operations in marketing and consumer behavior. The book provides a reconstructed version of celeb endorsement appropriate for the cutting-edge virtual advertising generation, increasing the traditional triad—attractiveness, trustworthiness, and expertise—to include popularity and relevance. Through a rigorous empirical framework and structural equation modeling, the author demonstrates the importance of these five dimensions in shaping consumer attitudes, brand perceptions, and purchase intentions. This overview evaluates the book’s conceptual contributions, methodological rigor, managerial relevance, and contextual barriers, supplying insights for academics, marketers, and future research directions. The study concludes that the book provides a extensive and timely contribution to marketing literature and practice in emerging economies.